Sport, Violence, and Masculinity in Norbert Elias and Eric Dunning. A Reading Oriented Towards the School Settting - Patierno, Nicolás (2021)
This paper aims to analyze sport and violence with special reference to football, denaturing those representations by which it is presumed that this practice can be considered “violent” in itself. In contrast, and following the contributions of Norbert Elias and Eric Dunning, we understand football and violence as antagonistic categories, since in explicit agreement with the hypothesis of these authors, one of the original purposes of sport is the mitigation of violence. We will try to retrace the paths by which football has been stigmatized by discouraging its practice in some educational fields. Complementarily, we will study the influence of some constitutive categories of the problem posed, such as masculinity, fanaticism, “football stamina” and media sensationalism, among others. Following this line, the conclusion invites us to recover the educational value of sport, more precisely, its relevance in the processes of socialization and recognition of the rules.